Small Laser-Textured Dimples for Improved Tribological Performance of CoCrMo in Artificial Hip Joints - William B. Bennett; Min Zou (Lubricants)
This study investigates the impact of small dimples on the tribological properties of CoCrMo (CCM) surfaces. Laser-ablated textures with 5 µm diameter dimples were fabricated at varying aspect ratios (0.1, 0.2, 0.3) and surface densities (5%, 15%, 25%) to evaluate their effects on friction and wear when paired with ultra-high molecular weight polyethylene (UHMWPE) counterfaces. The results showed that small dimples significantly reduced and stabilized the coefficient of friction (CoF) and wear compared to untextured CCM and larger dimples as reported in the literature. The texture configuration with a 5% surface density and 0.1 aspect ratio achieved the best combination of friction and wear performance by facilitating the formation of a stable and uniform lubricant film during sliding. These findings underscore the potential of small, precisely engineered surface textures to improve the tribological performance of CCM, offering a promising approach for reducing friction and wear in artificial hip joints.